Unused medicine take-back programmes: a systematic review - Leong Seng Wang; Zoriah Aziz; Ee Syuen Wang; Zamri Chik (Taylor & Francis Group, 2024)
Background: Improper disposal of unused medicine can impact the environment causing significant healthcare and financial burdens. While the medicine take-back programme is an effective management strategy, its effectiveness differs across countries. This study aimed to systematically review the take-back programmes in various countries and to identify areas needing improvement for programme enhancement.Methods: We conducted searches in Medline, EMBASE, CINAHL, Web of Science, Scopus, and Google Scholar, from database inception to June 2023.Results: The review included 27 studies spanning 15 countries' medicine take-back programmes. While some programmes, mostly observed in the USA, were conducted at the local level with non-health-associated facilities, others were done at the national level within healthcare facilities. The cost of collected medicines ranged from US$7,416 to US$1,118,020, primarily involving medicines related to the nervous system, cardiovascular system, alimentary tract, and metabolism. Legislations pertaining to these programmes were available in the USA, most European countries, and Mexico, but unavailable in Spain, Austria, Australia, and New Zealand. However, despite this, the government or the industry in these countries managed the programmes.Conclusion: Well-structured take-back programmes featuring easily accessible collection points, regular collection schedules, clear programme ownership, with legislation defining financial responsibilities, showed positive outcomes.